STUDIES ON THE MEDICINAL USES OF WILD TREES OF NAGPUR DISTRICT: Life Sciences-Botany - MAURYA, RUPESH; DONGARWAR, NITIN (International Journal of Life Science and Pharma Research, 2012)
Medicinal trees have been used both in the prevention and cure of various diseases of humans and their pets with the advent of human civilization many system of therapy have been developed primarily based on plants. Ayurveda, Homeopathy, Siddha, Unani, are our traditional system of medicines. During the survey 64 plants taxa belonged to 57 genera under 32 families were mentioned by them having medicinal potential. Different plants parts of different species are used as medicine for treating various diseases. For each species, the following information is provided: Family, Common name, Medicinal uses. Most of the reported medicinal plants are effective in antihelmintic, antiseptic, antidysenteric, skin diseases, hypertension, antiviral, stomachic, piles, jaundice and antiseptic activities.